2013
DOI: 10.1093/nar/gkt389
|View full text |Cite
|
Sign up to set email alerts
|

aLeaves facilitates on-demand exploration of metazoan gene family trees on MAFFT sequence alignment server with enhanced interactivity

Abstract: We report a new web server, aLeaves (http://aleaves.cdb.riken.jp/), for homologue collection from diverse animal genomes. In molecular comparative studies involving multiple species, orthology identification is the basis on which most subsequent biological analyses rely. It can be achieved most accurately by explicit phylogenetic inference. More and more species are subjected to large-scale sequencing, but the resultant resources are scattered in independent project-based, and multi-species, but separate, web … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
440
0
5

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 640 publications
(445 citation statements)
references
References 41 publications
0
440
0
5
Order By: Relevance
“…Alignments of SIT and SIT-L sequences were created using MAFFT L-INS-i v7 (Katoh et al 2005; Kuraku et al 2013) with a gap opening penalty of 3 and offset value of 1. The short SIT-L sequences from Collozoum sp., S. streptacantha , and Halocynthia roretzi , and the very long Florenciella sp.…”
Section: Methodsmentioning
confidence: 99%
“…Alignments of SIT and SIT-L sequences were created using MAFFT L-INS-i v7 (Katoh et al 2005; Kuraku et al 2013) with a gap opening penalty of 3 and offset value of 1. The short SIT-L sequences from Collozoum sp., S. streptacantha , and Halocynthia roretzi , and the very long Florenciella sp.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, it has previously been shown that human sequences fall at multiple places across the WNV phylogeny (23). Sequence alignment was performed using MAFFT (32), and these results were inspected manually. This resulted in a total of 696 unique WNV genome sequences of 10,299 nucleotides in length (298 sequences from this study and 398 from GenBank; see Table S1 in the supplemental material).…”
Section: Methodsmentioning
confidence: 99%
“…The phylogenetic tree was constructed by means of the neighbor-joining method, including all gap-free sites and a Jukes-Cantor substitution model using the MAFFT version 7 online software (http://mafft.cbrc.jp/alignment/software/) (22). The reliability of the various inferred clades was estimated by bootstrapping (1,000 replicates).…”
Section: Methodsmentioning
confidence: 99%